SISTEM RESERVASI ONLINE UNTUK ANTRIAN BENGKEL MOTOR MENGGUNAKAN METODE EXTREME PROGRAMMING (Studi kasus : BUDI MOTOR SPORT ) - Lutfi Aryawirayudha Santoso; Dadan Mulyana; Tuti Rohayati (Jurnal Mahasiswa Sistem Informasi Galuh, 2026)
This study aims to design and develop a web-based motorcycle workshop queue reservation system for the SME Budi Motor Sport to improve service efficiency and address issues related to manual record-keeping. The current system still relies on conventional methods using paper-based records, which are prone to errors, data loss, and inefficiencies in reservation management. The research methods employed include observation, interviews, and literature review to identify system requirements. System development was carried out using the Extreme Programming (XP) method, which consists of planning, design, coding, and testing phases. The system was designed using UML modeling, including use case diagrams, activity diagrams, sequence diagrams, and class diagrams. The system was implemented using PHP programming language, supported by HTML, CSS, JavaScript, and a MySQL database. The results of this study indicate that the web-based reservation system facilitates customers in making online bookings, improves the operational efficiency of the workshop, and minimizes recording errors. Additionally, the system provides features for managing reservation data and enabling communication between customers and the workshop.